Implementasi Omotenashi Dalam Penyelenggaraan Enkai di Hotel Nikko Alivila Yomitan Resort Okinawa - Putu Arya Prananda; Ni Nengah Suartini (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2025)
This study aims to describe the implementation of omotenashi in the organization of enkai events particularly wedding receptions at Hotel Nikko Alivila Yomitan Resort in Okinawa, Japan. This is a qualitative descriptive study that uses the concept of omotenashi, the Japanese tradition of hospitality, as its theoretical framework. Data were collected through triangulation methods, (1) participatory observation at Hotel Nikko Alivila, (2) examination of the Standard Operating Procedures (SOPs), and (3) interviews conducted with the enkai manager. The findings reveal that omotenashi is implemented in enkai events such as wedding receptions in three key areas, 1) through event supporting elements, including table arrangements, table settings, and venue decorations, 2) through the direct services provided by the enkai staff and 3) through indirect hospitality efforts carried out by the enkai staff. The implementation of omotenashi in wedding reception enkai reflects the concept of ichi go ichi e, emphasizing the importance of creating a meaningful and memorable first impression for both the couple and their guests.